Increasing the concentration of plasma molecules improves the biological activity of platelet-rich plasma for tissue regeneration - Mikel Sánchez; Jon Mercader Ruiz; Daniel Marijuán Pinel; Pello Sánchez; Nicolás Fiz; Jorge Guadilla; Juan Azofra; Maider Beitia; Diego Delgado (Scientific Reports)
Abstract Platelet-rich plasma (PRP) has emerged as a promising therapy in a variety of medical fields. However, it is crucial to go beyond simple platelet concentration and examine the complex molecular composition both inside and outside platelets. The present work studies the effectiveness of a novel type of PRP named ‘balanced protein-concentrate plasma’ (BPCP). Different growth factor (GF) levels were measured using Enzyme Linked Immunosorbent Assay (ELISA), and in addition to the increase in intra-platelet GFs found in standard PRP (sPRP), BPCP also showed a higher concentration of plasmatic protein. Furthermore, extracellular vesicle (EV) concentration was significantly higher in BPCP. Cell proliferation was higher in cells incubated with lysates derived from BPCP compared to those cultured with sPRP. Regarding cell migration capacity, it was found that the process is platelet-dependent. Finally, the anti-inflammatory effect of BPCP was evaluated by inducing an inflammatory environment in M1-type macrophages. Cytokine levels were measured by ELISA following BPCP administration, showing a significant decrease in pro-inflammatory IL-1β, IL-6 and TNF-α. In summary, although further preclinical and clinical studies are needed in order to determine the therapeutic potential of BPCP, this PRP with unique characteristics demonstrates encouraging in vitro results that could potentially enhance tissue regeneration capacity.